Oligomerization of a retroviral matrix protein is facilitated by backbone flexibility on nanosecond time scale - Srb, Pavel; Vlach, Jiří; Prchal, Jan; Grocký, Marián; Ruml, Tomáš; Lang, Jan; Hrabal, Richard (The journal of physical chemistry. B, 2011)
The oligomerization capacity of the retroviral matrix protein is an important feature that affects assembly of immature virions and their interaction with cellular membrane. A combination of NMR relaxation measurements and advanced analysis of molecular dynamics simulation trajectory provided an unprecedentedly detailed insight into internal mobility of matrix proteins of the Mason-Pfizer monkey virus. Strong evidence have been obtained that the oligomerization capacity of the wild-type matrix protein is closely related to the enhanced dynamics of several parts of its backbone on a nanosecond time scale. Increased flexibility has been observed for two regions: the loop between α-helices α2 and α3 and the C-terminal half of α-helix α3 which accommodate amino acid residues that form the oligomerization interface. On the other hand, matrix mutant R55F that has changed structure and does not exhibit any specific oligomerization in solution was found considerably more rigid. Our results document that conformational selection mechanism together with induced fit and favorable structural preorganization play an important role in the control of the oligomerization process.
Keywords: aminokyseliny; Masonův-Pfizerův opičí virus; Amino Acids; simulace molekulární dynamiky; Amino Acid Substitution; Protein Multimerization; Viral Matrix Proteins; proteiny virové matrix; Mason-Pfizer monkey virus; substituce aminokyselin; Protein Structure, Quaternary; Molecular Dynamics Simulation; kvarterní struktura proteinů; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; multimerizace proteinu